Interrelations Between Ceruloplasmin and Fe Status During Human Pregnancy - Fosset, Cédric; McGaw, Brian A.; Abramovich, David; McArdle, Harry J. (Biological trace element research, 2004)
It is well established that Fe and ceruloplasmin interact in animals and in in vitro models. However, Fe-mediated regulation of ceruloplasmin has never been investigated in humans. In an observational study, 53 pregnant women aged 19-39 yr (29.8 +/- 0.7 yr, mean +/- SEM) were recruited at the Aberdeen Antenatal Clinic, Aberdeen Maternity Hospital, UK. All requirements for local ethical committees were followed. Venous blood samples were taken from each woman at 34 wk gestation for measurement of Fe status and ceruloplasmin. Various parameters were used to test for Fe status. The most sensitive one appeared to be soluble transferrin receptor, which increased with parity. In the population studied, there was no relationship between hemoglobin or ferritin and serum ceruloplasmin. However, using soluble transferrin receptor (sTfR) levels, we were able to demonstrate an inverse linear relationship (r = 0.37, p = 0.021, n = 41) between Fe status and ceruloplasmin. Fe supplementation, number of previous pregnancies, and smoking habits did not affect this relationship. Our data support in vitro results showing regulation of ceruloplasmin by Fe and also suggest that the interactions between Fe and ceruloplasmin should be considered when Fe supplementation is given.